Correct option is the second option, B
The given expression is 2x-3 .
So when x =1, we will get 2(1)-3 = 2-3 =-1
When x=2, we will get, 2(2) -3 = 4-3 =1
When x=3, we will get 2(3)-3 = 6-3=3
When x=4, we will get 2(4)-3 = 8-3=5
So the required result of the expansion is -1+1+3+5=8
Correct option is the second option .
Writing out the series for n = 0, 1, 2, 3, we have ...
(2) +(x +2) +(2x +2) +(3x +2) = 6x +8
B on edge (15.5)
The answer on edge is C) 6x + 8 I hope this helps
When I am in the front of the world I wanna is this morning for me a little more than welcome is a great
Given , We know that indicates that we need to start with and finish with ,
In order to expand the series, the procedure is the following:
This result matches with the third option.